2004
DOI: 10.1002/humu.9239
|View full text |Cite
|
Sign up to set email alerts
|

OCRLMutation analysis in Italian patients with Lowe syndrome

Abstract: The oculocerebrorenal syndrome of Lowe (OCRL, also called OCRL1) is a rare X-linked disorder characterized by major abnormalities of eyes, nervous system, and kidneys. The gene responsible for OCRL was identified by positional cloning and encodes an inositol polyphosphate-5-phosphatase. We performed the molecular analysis in 9 Italian patients and 26 relatives and we detected the mutations in all the examined patients. Eight mutations out of nine had never been described and consisted of truncating mutations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…We have previously shown that the ΔE585, I768N, and A797P mutations abolish binding to, and co-localization with APPL1, while retaining binding to Rac and clathrin [11]. Mutant forms of the COOH-terminal region of OCRL harboring the three other mutations, V577E [17], L687P (B. Roa unpublished data, http://research.nhgri.nih.gov/lowe/), and C679W, were tested for protein interactions in GST pulldown assays. None of these mutant proteins bound to APPL1 (Fig.…”
Section: Ocrl Patient Mutations Abolish Binding To Appl1mentioning
confidence: 99%
“…We have previously shown that the ΔE585, I768N, and A797P mutations abolish binding to, and co-localization with APPL1, while retaining binding to Rac and clathrin [11]. Mutant forms of the COOH-terminal region of OCRL harboring the three other mutations, V577E [17], L687P (B. Roa unpublished data, http://research.nhgri.nih.gov/lowe/), and C679W, were tested for protein interactions in GST pulldown assays. None of these mutant proteins bound to APPL1 (Fig.…”
Section: Ocrl Patient Mutations Abolish Binding To Appl1mentioning
confidence: 99%
“…Lowe syndrome is transmitted as an X-linked recessive trait with a high rate of new mutations, which are responsible for about one-third of the cases (Lin et al 1997;Addis et al 2004). However, several females showing the complete typical clinical manifestations of the syndrome have been described (Scholten 1960;Svore et al 1967;Harris et al 1979;Sagel et al 1970;Yamashina 1981;Hodgson et al 1986;Mü ller et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The 23 coding exons and their flanking intronic sequences of OCRL1 gene were amplified from genomic DNA using forward and reverse primers designed according to nucleotide sequences (Addis et al 2004). …”
Section: Ocrl1 Sequencingmentioning
confidence: 99%
“…Excepting very few cases, the OCRL mutations associated with Dent disease 2 do not overlap with those causing Lowe syndrome. 10,20,24 Missense mutations occur in the middle region of the gene (exons 9-15), whereas truncating mutations are found exclusively in the first 7 exons; the OCRL mutations associated with Lowe syndrome are located instead in the 3 0 region of the gene (exons [9][10][11][12][13][14][15][16][17][18][19][20][21][22] and involve all three functional OCRL1 domains, whereas frameshift and nonsense mutations cluster in exons [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The different distribution of OCRL mutations in Dent disease 2 and Lowe syndrome suggests a genotype-phenotype correlation that has yet to be thoroughly explored.…”
Section: Resultsmentioning
confidence: 99%
“…Sequences of all 23 coding exons and the flanking intronic sequence of the human OCRL gene were analyzed according to Addis et al 22 The nomenclature of the mutations is based on the cDNA sequence NM_000276.3.…”
Section: Case Reportmentioning
confidence: 99%